Validation of chemical compound library screening for transcriptional co‐activator with PDZ‐binding motif inhibitors using GFP‐fused transcriptional co‐activator with PDZ‐binding motif - Nagashima, Shunta (Cancer Sci, 2016)
Transcriptional co‐activator with PDZ‐binding motif (TAZ) plays versatile roles in cell proliferation and differentiation. It is phosphorylated by large tumor suppressor kinases, the core kinases of the tumor‐suppressive Hippo pathway. Phosphorylation induces the cytoplasmic accumulation of TAZ and its degradation. In human cancers, the deregulation of the Hippo pathway and gene amplification enhance TAZ activity. TAZ interacts with TEA domain family members (TEAD), and upregulates genes implicated in epithelial–mesenchymal transition. It also confers stemness to cancer cells. Thus, TAZ activation provides cancer cells with malignant properties and worsens the clinical prognosis. Therefore, TAZ attracts attention as a therapeutic target in cancer therapy. We applied 18 606 small chemical compounds to human osteosarcoma U2OS cells expressing GFP‐fused TAZ (GFP‐TAZ), monitored the subcellular localization of GFP‐TAZ, and selected 33 compounds that shifted GFP‐TAZ to the cytoplasm. Unexpectedly, only a limited number of compounds suppressed TAZ‐mediated enhancement of TEAD‐responsive reporter activity. Moreover, the compounds that weakened TEAD reporter activity did not necessarily decrease the unphosphorylated TAZ. In this study, we focused on three compounds that decreased both TEAD reporter activity and unphosphorylated TAZ, and treated several human cancer cells with these compounds. One compound did not show a remarkable effect, whereas the other two compounds compromised the cell viability in certain cancer cells. In conclusion, the GFP‐TAZ‐based assay can be used as the first screening for compounds that inhibit TAZ and show anticancer properties. To develop anticancer drugs, we need additional assays to select the compounds.